Application of micropaleontological and chemostratigraphic analyses: Insight into depositional environment and hydrocarbon prospectivity in the Niger Delta Basin, Nigeria - N.S. Igbinigie; G.O. Aigbadon (Results in Earth Sciences, 2025)
The Niger Delta Basin, one of the world's most prolific hydrocarbon provinces, presents significant challenges in stratigraphic correlation and reservoir characterisation due to its structural and depositional complexities. This study presents an integrated analysis of the Miocene sediments that penetrated the NS-2 well in Leuma Field, Coastal Swamp Depobelt. The research integrates micropaleontological, palynological, and chemostratigraphic data, which was lacking in the study area to interpret the depositional environments and hydrocarbon prospectivity of the studied interval. A total of 102 ditch-cutting samples were analysed for lithofacies characteristics, foraminiferal assemblages, palynomorph distributions, and geochemical compositions. Lithofacies analysis reveals alternating sandy and shaly intervals, indicative of a transitional to paralic environment associated with deltaic and shallow marine settings. Micropaleontological data highlight the dominance of benthic foraminifera, including Uvigerina subperegrina and Lenticulina grandis, supporting shallow marine depositional conditions with intermittent marine incursions. Palynological results reveal a humid tropical paleoclimate, characterised by mangrove pollen such as Zonocostites ramonae and Acrostichum aureum, contributing to organic-rich sediments. Chemostratigraphic analysis indicates high SiO₂ concentrations (up to 90.4 %) in sandy intervals, suggesting high-energy depositional settings, while elevated trace elements in shales reflect low-energy, reducing conditions. These findings reflect the interplay of climatic oscillations, tectonics, and sea-level fluctuations in shaping the stratigraphy and hydrocarbon systems of the study area. The results demonstrate a favourable petroleum system characterised by organic-rich source rocks, high-quality reservoirs, and effective traps, enhancing the hydrocarbon prospectivity of the Agbada Formation in the NS-2 well in the study area of the basin.